Determinan Permintaan dan Penawaran Kopi Robusta di Indonesia: Analisis Ekonometrik : Determinants of Demand and Supply for Robusta Coffee in Indonesia: Econometric Analysis - Harya, Gyska Indah; Mubarokah, Mubarokah; Widayanti , Sri; Hariati, Hariati; Inti, Ristani Widya; Mahiro, Septiana Dina (Jurnal Ilmiah Manajemen Agribisnis, 2025)
This study analyzes the supply and demand of Indonesian robusta coffee over the past 10 years. Multiple linear regression analysis results indicate that on the demand side, only per capita income has a significant influence, while coffee price and population are insignificant. On the supply side, coffee price, harvested area, and productivity variables are found to have significant effects. Classical assumption tests indicate multicollinearity and autocorrelation issues in the model. Overall, the study concludes that robusta coffee supply is strongly influenced by production factors (land and productivity), while demand is more influenced by purchasing power (per capita income) than by price. These findings provide important insights for stakeholders to improve the competitiveness and welfare of Indonesian robusta coffee commodities.